2012
DOI: 10.1523/jneurosci.2033-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Learning Acts on Distinct Processes for Visual Form Perception in the Human Brain

Abstract: Learning is known to facilitate our ability to detect targets in clutter and optimize brain processes for successful visual recognition. Previous brain-imaging studies have focused on identifying spatial patterns (i.e., brain areas) that change with learning, implicating occipitotemporal and frontoparietal areas. However, little is known about the interactions within this network that mediate learningdependent improvement in complex perceptual tasks (i.e., discrimination of visual forms in clutter). Here we ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 96 publications
2
46
0
Order By: Relevance
“…As reviewed in the Introduction, many studies implicated V1 as the locus of neural plasticity underlying visual learning (Schoups et al, 2001;Schwartz et al, 2002; Furmanski et al, 2004; Yotsumoto et al, 2008; Gilbert et al, 2009;Bao et al, 2010; Jehee et al, 2012), while other studies showed plasticity of representations in extrastriate visual (Zohary et al, 1994; Tovee et al, 1996;Raiguel et al, 2006), somatosensory (Recanzone et al, 1992 b,c,d;Harris et al, 1999) and auditory (Recanzone et al, 1993;Alain et al, 2007;van Wassenhove and Nagarajan, 2007) cortex. However, others found that pertinent changes were modest in visual cortical areas (Ghose et al, 2002;Yang and Maunsell, 2004), were not confined to early visual areas (Song et al, 2002; Ding et al, 2003;Mayhew et al, 2012), or affected the decision stage rather than sensory representations (Law and Gold, 2008). These neurophysiological studies, along with psychophysical and modeling studies (Petrov et al, 2005; Bejjanki et al, 2011;Huang et al, 2012) favor an alternative hypothesis, that perceptual learning depends on plasticity of perceptual readout by decision processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reviewed in the Introduction, many studies implicated V1 as the locus of neural plasticity underlying visual learning (Schoups et al, 2001;Schwartz et al, 2002; Furmanski et al, 2004; Yotsumoto et al, 2008; Gilbert et al, 2009;Bao et al, 2010; Jehee et al, 2012), while other studies showed plasticity of representations in extrastriate visual (Zohary et al, 1994; Tovee et al, 1996;Raiguel et al, 2006), somatosensory (Recanzone et al, 1992 b,c,d;Harris et al, 1999) and auditory (Recanzone et al, 1993;Alain et al, 2007;van Wassenhove and Nagarajan, 2007) cortex. However, others found that pertinent changes were modest in visual cortical areas (Ghose et al, 2002;Yang and Maunsell, 2004), were not confined to early visual areas (Song et al, 2002; Ding et al, 2003;Mayhew et al, 2012), or affected the decision stage rather than sensory representations (Law and Gold, 2008). These neurophysiological studies, along with psychophysical and modeling studies (Petrov et al, 2005; Bejjanki et al, 2011;Huang et al, 2012) favor an alternative hypothesis, that perceptual learning depends on plasticity of perceptual readout by decision processes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, other fMRI methods, e.g., based on multivoxel pattern analysis, or fine-grained analysis of digit maps (Duncan and Boynton, 2007) might demonstrate somatosensory cortical plasticity in our task, as might methods using alternative modalities such as electrophysiology. Indeed, somatosensory cortical plasticity occurs in other tasks (see above), and changes in both sensory representations and decision processes may be relevant (Bejjanki et al, 2011;Mayhew et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…We do not have the space here to discuss what is known about the development [193] and learning of biological visual processing hierarchies (e.g., [105], [113]). However, there are some fairly obvious conclusions relevant to computer vision.…”
Section: Development and Learning Of Visual Processing Hierarchiesmentioning
confidence: 99%
“…Alarmingly, the presented pattern of spurious motion related EEG-BOLD effects was found employing preprocessing steps and analysis steps commonly employed in EEG-fMRI (Baumeister et al, 2014;de Munck et al, 2007;de Munck et al, 2009;Debener et al, 2007;Hanslmayr et al, 2013;Hanslmayr et al, 2011;Jann et al, 2009;Jansen et al, 2012;Laufs et al, 2006b;Laufs et al, 2003;Li et al, 2012;Liu et al, 2012b;Mayhew et al, 2010;Mayhew et al, 2012;Mayhew et al, 2013;Meyer et al, 2013;Novitskiy et al, 2011;Plichta et al, 2013;Regenbogen et al, 2012;White et al, 2013) and could easily pass as neurophysiological plausible results. The relationship of theta oscillatory power and successful memory formation remains controversial, as opposing effects have been reported by recent studies (Hanslmayr and Staudigl, 2014).…”
Section: Motion Causes Seemingly Neurophysiological Plausible Effectsmentioning
confidence: 99%